An efficient, economical, and easy mass production biochar supported zero˗valent iron composite derived from direct˗reduction natural goethite for Cu(II) and Cr(VI) remove. (December 2021) - Cai, Miao; Zeng, Jian; Chen, Yaozong; He, Peng; Chen, Fang; Wang, Xu; Liang, Jinye; Gu, Chunyao; Huang, Dongli; Zhang, Ke; Gan, Min; Zhu, Jianyu
Abstract: In this study, a novel biochar-supported zero-valent iron (ZVI) composite was synthesised by a one-pot co-pyrolysis reduction method, and was used to remove Cu(II) and Cr(VI). The raw materials for the composite were derived from natural bagasse/straw and goethite. Scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, Fourier-transform infrared (FTIR) spectroscopy, thermogravimetry (TG), and Brunauer-Emmett-Teller (BET) analysis were used to characterise the biochar and biochar-supported ZVI composites. Batch removal experiments on the effects of the initial pH and citric acid concentrations were performed as well as kinetic studies and isotherm experiments. The composite materials showed better Cu(II) and Cr(VI) removal performance than single biochar and mineral. The removal of Cu(II) and Cr(VI) is pH-dependent, and proceeds via heterogeneous multilayer chemisorption. Electrochemical analysis revealed that straw biochar-supported ZVI composite exhibited greater electrical conductivity and electron transfer rate than pure biochar and ZVI. FTIR spectroscopy and X-ray photoelectron spectroscopy (XPS) elucidated the uptake mechanism, showing that Cu(II) and Cr(VI) were easily adsorbed onto the biochar surface and were then reduced by ZVI. These results indicate that biochar-supported ZVI composite is effective for heavy metal remediation, which is economical, environment-friendly, and suitable for mass production. Highlights: Biochar supported ZVI was fabricated from natural goethite through one-pot co-pyrolysis. Mineral based ZVI and Biochar showed synergistic effect on Cu(II)/Cr(VI) removal. Direct electron occurred between biochar and ZVI facilitated metals removal. Cu(II) and Cr(VI) remove were mainly through adsorption and reduction, respectively. The material is economical, environmentally friendly and easy to mass production.